Scanning Probe Microscopy электронный курс - Кузнецов, П. В. физик доцент Томского политехнического университета, кандидат физико-математических наук 1952- (TPU Moodle, 2019)
In the electronic course "Scanning probe microscopy" the fundamental principles of modern methods of scanning probe microscopy, primarily scanning tunneling microscopy (STM) and scanning force microscopy (SFM), both regarding theory and practice are considered. The physical foundation and theory of STM and SFM as well as the basic measurement modes are treated thoroughly. An overview of other SPM techniques is given. The main parts and the construction of scanning probe microscopes are considered, as well as the materials from which they are made. The course also dwells on advanced measurement and analysis methods, artefacts, as well as manipulation with STM and SFM. Several examples of the use of SPM techniques in current research are given. The knowledge gained upon the course successful completion will allow students to choose an adequate method or SPM mode for studying surface properties in accordance with the research objectives, critically evaluate the data obtained in terms of the impact of possible artifacts, and process and analyze the results.